2012
DOI: 10.3324/haematol.2011.057372
|View full text |Cite
|
Sign up to set email alerts
|

CD20 positive cells are undetectable in the majority of multiple myeloma cell lines and are not associated with a cancer stem cell phenotype

Abstract: © F e r r a t a S t o r t i F o u n d a t i o nHIB19) and CD27-PE-Cy7 (clone O323) antibodies were purchased from eBioscience (San Diego CA, USA) and CD38-AlexaFluor700 antibody (clone HIT2) was obtained from Exbio (Vestec, Czech Republic). CD20 dim+ and CD20 -RPMI-8226 cells were extensively characterized. For real time quantitative PCR (qRT-PCR), total RNA was extracted from CD20 dim+ and CD20 -RPMI-8226 cells using an RNeasy Mini Kit (Qiagen, Valencia, USA) following the manufacturer's protocol. RNA quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 23 publications
1
28
1
Order By: Relevance
“…We read with interest the letter by Van Hoef 1 about the article by Paino et al 2 In that study, we were unable to identify a CD20 + population among 8 myeloma cell lines leading us to conclude that CD20 may not be a suitable antigen for the identification of myeloma cancer stem cells.…”
mentioning
confidence: 65%
“…We read with interest the letter by Van Hoef 1 about the article by Paino et al 2 In that study, we were unable to identify a CD20 + population among 8 myeloma cell lines leading us to conclude that CD20 may not be a suitable antigen for the identification of myeloma cancer stem cells.…”
mentioning
confidence: 65%
“…In patients, it was believed that CD20-CD138+ was the origin of clonogenic myeloma cells (Chiron et al, 2012). Moreover, some researchers could not detect CD20 positive cells in NCI-H929 cells and believed that CD20 positive cells were not associated with a cancer stem cell phenotype (Paíno et al, 2012). At present, the nature of clonogenic myeloma cells remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…It was showed that CD20+ and CD138-cells were not the mark of clonogenic cells (Jakubikova et al, 2011;Chiron et al, 2012;Hosen et al, 2012). Moreover, some study found that NCI-H929 cells did not contain CD20 positive cells and suggested that CD20 positive cells were not associated with a cancer stem cell phenotype (Paíno et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…During the last decade, MSCNET has performed detailed studies to confirm or refute previous studies [47][48][49][50][51][52][53][54][55][56][57][58][59][60] and established protocols 17,[61][62][63][64][65][66][67][68][69][70] to delineate the phenotypes of subpopulations of cells in randomly selected primary tumor samples and in preclinical disease models. While our investigations did not confirm that pre-PC B cells are myeloma initiating, 50 low/-memory B cells engrafted into human bone grafts, resulting in the repopulation of polyclonal B cells, which supports the hypothesis that memory B cells have the ability to self-renew.…”
Section: In Search Of the Mmscmentioning
confidence: 99%